2017
DOI: 10.1175/jas-d-16-0087.1
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Link between Ice Nucleating Particles Released in Nascent Sea Spray Aerosol and Oceanic Biological Activity during Two Mesocosm Experiments

Abstract: Emission rates and properties of ice nucleating particles (INPs) are required for proper representation of aerosol–cloud interactions in atmospheric models. Few investigations have quantified marine INP emissions, a potentially important INP source for remote oceanic regions. Previous studies have suggested INPs in sea spray aerosol (SSA) are linked to oceanic biological activity. This proposed link was explored in this study by measuring INP emissions from nascent SSA during phytoplankton blooms during two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
176
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(200 citation statements)
references
References 57 publications
15
176
1
Order By: Relevance
“…Determining the mass fraction of CO 3 2− with respect to total carbon is challenging without the availability of appropriate standards for the organic component. While it is possible for radiation damage to cause the appearance of C*O 3 in STXM chambers open to the air, 41 this was not observed during the course of these experiments; spectra for standard compounds showed no resolvable contribution from the C*O 3 transition. Furthermore, the STXM chamber used here was evacuated and backfilled with helium to avoid unwanted reaction of gases with particles in these studies.…”
Section: Resultsmentioning
confidence: 82%
“…Determining the mass fraction of CO 3 2− with respect to total carbon is challenging without the availability of appropriate standards for the organic component. While it is possible for radiation damage to cause the appearance of C*O 3 in STXM chambers open to the air, 41 this was not observed during the course of these experiments; spectra for standard compounds showed no resolvable contribution from the C*O 3 transition. Furthermore, the STXM chamber used here was evacuated and backfilled with helium to avoid unwanted reaction of gases with particles in these studies.…”
Section: Resultsmentioning
confidence: 82%
“…In addition to ongoing interest into the action of both mineral dusts and soot [6][7][8], the role of the soil organic matter, which includes INPs produced by the decomposer community, as a source of atmospheric INPs is now being more closely examined [9][10][11][12]; pioneering work identified the litter layer, in particular, as a prodigious source of biological INPs in diverse global ecotypes [13,14]. By contrast, while oceans comprise 71% of the Earth's surface area and emit INPs within sea spray-mainly by bubble bursting-they are only now being investigated more systematically [15][16][17][18][19][20][21]. Until recently, the only systematic study of INPs in the marine boundary layer was that undertaken by Bigg [22].…”
Section: Introductionmentioning
confidence: 99%
“…This value lies in the lower end of the range of factors recommended by Turpin and Lim (2001) for non-urban cites, and is chosen since we are only considering water insoluble organics, which are associated with lower carbon-to-molecule conversion in their study. Subsequent publications which investigated air borne sea spray aerosols produced in laboratory settings (DeMott et al, 2016;McCluskey et al, 2017) have, however, indicated much lower ice nucle-15 ation efficiencies than that described by Wilson et al (2015). Therefore a sensitivity study is also performed by producing a fit to data published in DeMott et al (2016).…”
Section: Heterogeneous Ice Nucleation Of Moamentioning
confidence: 88%
“…Suggested INP candidates, such as mineral dust, terrestrial biogenic material, and black carbon, are mostly of terrestrial origin. Recently, however, more interest has been drawn to oceans being possible sources of ice-5 active organic matter (Bigg, 1973;Knopf et al, 2011;Wang et al, 2015;Wilson et al, 2015;DeMott et al, 2016;McCluskey et al, 2017). While likely not as effective an INP as mineral dust, the difference in geographical locations of their emission sources may cause such marine organic aerosols (MOA) to become an important source of INPs in remote marine regions.…”
mentioning
confidence: 99%